Are Humanities Heading for Extinction? Analysis of Anthropocene Ecocriticism, Geo-Ecocriticism, and Islamecocriticism - Inas Samy Abolfotoh (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
Serious concerns have been circulating in academia regarding humanities and how they have been relegated to the backbenches. Data reveal a remarkable decline in submissions for humanities if compared to non-humanities. The current paper proposes that despite this decline, humanities have always been and will continue to be a moving force in shaping intellectual attitudes worldwide. To prove this standpoint, the author employs ecocriticism and eco-poetry as influential sub-disciplines of humanities. With the rocket-speed changeability of the present time, ecocriticism and eco-poetry play a crucial role in judging, evaluating, or even changing the course of cultural advancements if they venture into destructive paths. In other words, ecocritical theory is concerned with monitoring and unveiling versatile anthropocentric activities, most of which are destructive to nature. Fortunately, with the help of authors writing under the influence of ecocriticism, the devastation of many natural spots came to an end. Thus, the study begins by introducing some important phases of the ecocritical project like Anthropocene ecocriticism, Geo-ecocriticism, and Islamecocriticism. Then, an Islamecocritical analysis of "Lake Selby" by Canadian poet I. Layton is presented. The lake suffered from multiple ecological problems. However, the poem along with other scientific warnings successfully alerted the Canadian government. Consequently, the lake's condition improved. Both sections of the study affirm that humanities shape human culture, and they are real and valid disciplines that complement the work of non-humanities. The argument is qualitative, being concerned with literary criticism. Therefore, the research methodology is primarily analytical and descriptive.